Decreased Muscle Strength in Children With Repaired Tetralogy of Fallot: Relation With Exercise Capacity - Graziëlla Eshuis; Hiske van Duinen; Otto T. H. M. Lelieveld; Anneke K. Hegeman; Hessel Nijenhuis; Tineke P. Willems; Ann M. Hepping; Natasha Maurits; Gideon J. du Marchie Sarvaas; Rolf M. F. Berger (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The aim of this study is to describe muscle strength in pediatric patients with repaired tetralogy of Fallot compared with healthy peers and to analyze the correlation between muscle strength and peak oxygen uptake, exercise capacity (mL/min). Methods and Results A prospective, cross‐sectional study was carried out in the University Medical Center Groningen between March 2016 and December 2019, which included 8 ‐to‐19‐year‐old patients with repaired tetralogy of Fallot. Exclusion criteria comprised the following: Down syndrome, unstable pulmonary disease and severe scoliosis affecting pulmonary function, neuromuscular disease, and mental or physical limitations that prohibit the execution of the functional tests. Muscle strength was compared with 2 healthy pediatric cohorts from the Northern Netherlands. Handgrip strength, maximal voluntary isometric contraction, and dynamic muscle strength in correlation with peak oxygen uptake, exercise capacity (mL/min) were the main outcomes of the study. The 67 patients with repaired tetralogy of Fallot (42% female; aged 12.9 [interquartile range, 10.0–16.3] years old) were compared with healthy children. The patients showed reduced grip strength (z‐score [mean±SD] −1.5±1.2, P<0.001), and total muscle strength (z‐score −0.9±1.3, P<0.001). Dynamic strength (Bruininks‐Oseretsky test) was significantly reduced (z‐score −0.3±0.8, P=0.001), but running, speed, and agility were normal (z‐score 0.1±0.7, P=0.4). Univariate correlation analyses showed strong correlations between absolute peak oxygen uptake, exercise capacity (mL/min), and muscle strength (grip strength r=0.83, total muscle strength r=0.88; P<0.001). In multivariate analyses, including correction for age and sex, total muscle strength (B 0.3; P=0.009), and forced vital capacity (B 0.5; P=0.02) correlated with peak oxygen uptake, exercise capacity (mL/min), independent of conventional cardiovascular parameters. Conclusions Children with repaired tetralogy of Fallot show reduced muscle strength, which strongly correlated with their exercise performance.